Analisis Perbandingan Single Piston Dan Double Piston Terhadap Jarak Dan Waktu Pengereman Menggunakan Variasi Discbrake Pada Motor 125 Cc - Octa, Hakim; Mufarida, Nely Ana; Kosjoko, Kosjoko (Universitas Muhammadiyah Ponorogo, 2024)
Safety is a major factor in planning and designing road facilities. Various studies related to accident risk analysis have been carried out, but there are still not many practical applications, especially for accident risk analysis at priority intersections. The method used in this research is a data collection method using a braking test process using single piston and double piston with standard disc brake variations. and after market. This research is intended to compare the braking distance and time using a variation discbrake. The results of comparative testing of single piston and double piston using a standard discbrake and a variation discbrake show that the maximum discbrake performance is the variation discbrake because it has a lower average braking time and distance than the standard disc brake. On a single piston with a pressure of 2kg, the average travel distance was 0.27 m (11.53 m - 11.26 m) with a time of 0.39 s (2.75 s - 2.36 s). Meanwhile, with a double piston with a pressure of 2kg, the average distance traveled was 0.06 m (8.50 m - 8.44 m) with a time of 0.15 s (1.88 s - 1.73 s). Variations in single piston braking greatly influence the braking distance and time, an average of 0.27 m with a time of 0.39 s from the standard discbrake, and variations of the double piston discbrake have a distance and time of 0.06 m with a time of 0.15 s from the standard discbrake.